EKSPLORASI PRAKTIK GIZI IBU HAMIL DENGAN ANEMIA MELALUI PENDEKATAN NETNOGRAFI DI KOMUNITAS DARING - Yuliarti, Yayu (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2025)
Anemia during pregnancy remains a major public health concern in Indonesia. Despite the government's iron supplement programs, adherence to Iron-Folic Acid (IFA) tablets remains low due to side effects, cultural myths, and lack of contextual education. In the digital era, online communities serve as a new platform for sharing experiences and information about pregnancy. This study aims to explore the perceptions, practices, and barriers faced by pregnant women in managing anemia using a netnographic approach within digital communities. This qualitative study used netnography to collect data from five digital platforms (Facebook groups, parenting forums, Instagram, Twitter/X, and YouTube) between January and March 2025. Data were analyzed using Braun & Clarke’s thematic analysis approach. From 342 analyzed posts, three major themes emerged: (1) pregnant women's perceptions of anemia and concerns about fetal impacts, (2) practices related to IFA consumption and iron-rich diets influenced by food myths, and (3) barriers such as nausea, gastrointestinal side effects, misinformation, and lack of empathetic healthcare services. On the other hand, digital communities provided social support and adaptive strategies through shared narratives. Netnography offers authentic insights into the nutritional behavior dynamics of pregnant women. Community-based digital education, incorporating storytelling and peer experiences, can enhance adherence to IFA supplementation. This study highlights the need for empathetic health communication strategies and the engagement of influencers from digital mother communities. Limitations include lack of validation of user narratives and restricted platform coverage. Mixed-method studies are recommended to further explore sociocultural contexts.